Social Support and Patterns of Institutionalization Among Older Adults: A Longitudinal Study. Issue 12 (8th October 2019) - Oh, Anna; Patel, Kanan; Boscardin, W. John; Max, Wendy; Stephens, Caroline; Ritchie, Christine S.; Smith, Alexander K.
Abstract : OBJECTIVES: To identify participants living at home and to estimate the risk of their transition into an institutional setting. DESIGN: Prospective cohort study from the National Health and Aging Trends Study (NHATS), a nationally representative survey of US adults aged 65 and older. SETTING: US national sample. PARTICIPANTS: A total of 4712 NHATS participants were living at home in 2011. Residential transitions were described every year through 2017. MEASUREMENTS: The primary outcome was transition time into an institutional setting. Primary predictors were social support factors (living spouse, lives with others, presence of social network, and participation in social activities). Covariates included age, sex, race, cognitive status, functional disability, multimorbidity, and Medicaid enrollment. A Fine and Gray hazards model estimated the risk of transition into an institutional setting, with death before institutionalization considered a competing risk. RESULTS: In 2011, 4712 NHATS participants were living at home (78 ± 8 y; 57% female; 80% white; 10% probable dementia; 7% with three or more activities of daily living disabilities). By 2017, 58% remained at home, 17% had either transitioned to an institution or died in an institution, and 25% died before institutionalization. In multivariable analyses that adjusted for age, sex, race, cognitive status, functional disability, multimorbidity, and Medicaid enrollment, participants were more likely to move out of the home into an institution if they had no social network (0 vs three or more people; subhazard ratio [sHR] = 1.8; 95% confidence interval [CI] = 1.2–2.5; P = .003) or lived alone (sHR = 1.9; 95% CI = 1.6–2.2; P < .0001). Older adults who enjoyed going to the movies, dinner, or the casino and visiting family or friends had a lower probability of institutionalization compared with participants who did not enjoy these activities or did not visit family or friends (adjusted sHR = .7; 95% CI = .6–.9; adjusted sHR = .7; 95% CI = .6–.9, respectively). CONCLUSION: Policy initiatives should target older adults with limited social support to reduce the risk of moving from home into an institution. J Am Geriatr Soc 67:2622–2627, 2019